CHEMICAL CASTRATION PUNISHMENT: AN INTERNATIONAL HUMAN RIGHTS LAW PERSPECTIVE - Reza, M Hilmi Miftahzen; Kamila, Sultanshina (Realism: Law Review, 2025)
This research aims to determine international legal instruments in chemical castration cases and seen from a criminal and health perspective. This research is a norative-juridical type of research using conceptual methods. Data funds are used primary, secondary and tertiary. This research focuses on chemical castration from an international human rights perspective and health impacts. The results of this research in the form of chemical castration practitioners in Indonesia and abroad need to be re-examined from a human rights perspective to see whether the rights of the perpetrators have been violated because the legal action of chemical castration is a torturous and inhumane punishment so there is a lot of negative stigma and legalization of violations of human rights. Apart from that, the defendants' rights to health were violated